CYBER SECURITY OF RADIATION TESTS OF SPACE VEHICLES: LEGAL FRAMEWORK, REGULATORY REQUIREMENTS AND THE STATE OF THEIR INNOVATIVE SUPPORT - Біленчук, Петро Дмитрович; Малій, Микола Іванович; Сватюк, Наталія Іванівна; Симканич, Олеся Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to study the regulatory and legal status of the radiation research, methodological support and hardware capabilities for the organization of radiation testing of materials and devices for space use in the earthly conditions. Methods: review of available databases on ionization factors of outer space, Earth’s radiation belts, methods of the accelerated radiation tests, mathematical modeling and field studies of radiation defect formation in the structural materials of spacecraft conducted on nuclear particle accelerators, in particular, the M-30 microtron, that imitates the penetrating cosmic radiation on the space materials and devices. Discussion: if the M-30 microtron is used as a stand for radiation tests, it is necessary to study the metrological characteristics of its radiation fields, fix the stages and sequence of their implementation to ensure radiation tests of high-energy electrons that mimic the factors of outer space. It is important to harmonize domestic and international regulations for radiation testing, in particular, in terms of the sequence of operations and dosimetry monitoring of radiation. Results: the radiation stand based on the M-30 microtron is capable to simulate the parameters of hard space radiation, and it is possible to organize tests to establish the radiation resistance of the materials and space technology devices in accordance with the regulatory requirements. The radiation stands that are capable to conduct the earthly tests of spacecraft should be incorporated into the register of the National Control and Testing Center. The authors conclude that today in Ukraine there are a number of legal documents governing the conduct of radiation tests of space equipment. There is a legal, methodological and scientific-technological base that allows to conduct extremely important radiation tests of materials and devices for space use. In addition, the availability of certified radiation fields allows for promising research in the field of space materials science, as well as to investigate the effectiveness of passive protection systems and optimization of the layout of space equipment.